2016
DOI: 10.20336/rbs.157
|View full text |Cite
|
Sign up to set email alerts
|

Reincidência criminal e penitenciária: aspectos conceituais, metodológicos, políticos e ideológicos

Abstract: RESUMOLevando em consideração que hoje no Brasil não se possuem informações consistentes sobre a reincidência de egressos penitenciários e que, sem qualquer fundamentação empírica, é identificada como alta, este artigo tem como objetivo promover reflexões sobre questões conceituais, metodológicas e ideoló-gicas que envolvem o tema reincidência criminal e penitenciária. Pretende-se investir inicialmente na compreensão das informações divulgadas por algumas pesquisas, principalmente procurando entender os concei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…With regard to religiosity, even though the evidence indicates that it acts as a protective factor for the presence of suicidal ideation, in this study it was not possible to make such confirmation, since there was no statistically significant correlation (p=0.477/POR=0.941), in accordance with other authors ( 12 - 46 ) . There is still no evidence that religiosity significantly reduces suicide in prison, and it is suggested that perhaps this is due to the absence of studies that specifically address the impact of religiosity on the mental health of the FDP ( 42 , 47 ) .…”
Section: Discussionsupporting
confidence: 56%
“…With regard to religiosity, even though the evidence indicates that it acts as a protective factor for the presence of suicidal ideation, in this study it was not possible to make such confirmation, since there was no statistically significant correlation (p=0.477/POR=0.941), in accordance with other authors ( 12 - 46 ) . There is still no evidence that religiosity significantly reduces suicide in prison, and it is suggested that perhaps this is due to the absence of studies that specifically address the impact of religiosity on the mental health of the FDP ( 42 , 47 ) .…”
Section: Discussionsupporting
confidence: 56%
“…Recidivism has a sizeable societal cost associated with incarceration, police wages, and legal expenses, a slight decrease in recidivism rates can produce significant cost savings (Bloom 2006). Therefore, projects that involve social reintegration should use recidivism as a quality indicator (Julião 2016).…”
Section: Discussionmentioning
confidence: 99%